INFLUENCE OF COMPANY AGE, GOOD CORPORATE GOVERNANCE, PRACTICES AND FINANCIAL PERFORMANCE ON INTERNET FINANCIAL REPORTING (IFR) (Empirical Study on Company LQ45 Year 2017 - 2019) - Asri Mustika Rosa; Apollo Daito (Jurnal Apresiasi Ekonomi, 2025)
Financial reporting on the internet is voluntary. There are no specific regulations governing IFR disclosure, so there is a gap in IFR practices between companies. This causes differences in the quality of reporting submitted by companies on their websites. The primary objective of this study is to investigate how the age of a company, effective corporate governance practices, and financial performance impact the extent of Internet Financial Reporting (IFR) disclosure. The data for this study was gathered from www.idx.co.id and company websites. The target population consisted of companies listed in the LQ45 index during August 2019. The sampling method employed was purposive sampling, resulting in 28 out of 45 companies meeting the criteria for inclusion in the study sample.   Multiple regression analysis using SPSS 27 software was utilized to analyze the data. The findings of the study suggest that leverage plays a significant role in determining the level of Internet Financial Reporting (IFR) disclosure, while factors such as company age, Good Corporate Governance practices, and profitability do not seem to have an impact on the extent of IFR disclosure.